Studi Literatur Pemodelan Smart-Posyandu sebagai Platform Pengawasan dan Pencegahan Stunting pada Anak - Ramayanti, Desi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
This study examines the implementation of the Smart-Posyandu platform as an innovative solution for monitoring and controlling stunting in children under five years old (toddlers) in Indonesia. The primary focus is on addressing the challenge of stunting, an indicator of developmental failure in toddlers, often caused by inadequate nutrition and repeated infections. The research findings indicate that the implementation of Smart-Posyandu, with features such as monitoring child growth, managing nutritional status, educating pregnant women on nutrition, and integrating with health services, can enhance the effectiveness of monitoring and intervening in stunting. The study also highlights the importance of collaboration among healthcare workers, the community, and the government in stunting prevention efforts. Recommendations include field implementation of the application, raising community awareness, integrating health systems, developing technology, and strategic collaboration. These findings contribute to the knowledge of applying information technology in public health and support the vision of Smart Government development in Indonesia, particularly in efforts to improve toddler health and reduce stunting.